Noelle MERING, Awake, Not Woke: A Christian Response to the Cult of Progressive Ideology, Gastonia: TAN Books, 2021, 256 pp. 14 x 22, ISBN 978-15-0511-842-5. - Paladino, M.-Soledad (Scripta Theologica, 2023)
Book Review